Political Imagination and Social Change - Salmenniemi, Suvi; Perheentupa, Inna; Ylostalo, Hanna (SAGE PUBLICATIONS LTD, 2025)
This Introduction to the special issue 'Political Imagination and Social Change' addresses the role of political imagination for transformative politics and social change. It argues that sociology has a critical role to play in analysing, theorising, and facilitating political imagination and contributing to reinvigorating the collective political imagination by offering insights to envisaging alternative social formations and destabilising conventional ways of thinking. The Introduction discusses how political alternatives are imagined, practised, and lived out in different historical, social, and geographical contexts and by different groups of people. It shows how structures of power and domination, such as colonialism, racism, and gender and class systems, shape the practices of political imagination and affect the ways in which people can imagine and act towards social change. It also discusses how political imagination can be methodologically approached, and proposes a tripartite conceptualisation of political imagination centring on the notions of utopia, imaginary, and practice. It concludes that emancipatory and progressive political imagination is sorely needed to counter today's dystopic and destructive forces and envisage better ways of being.